A data analytics mindset with Crisp-Dm - O'Hara, Richard; Haylon, Lisa S.; Boyle, Douglas M. (Strategic Finance, 2023)
According to a 2020 survey of 600 senior executives conducted by Harvard Business Review, 55% of organizations agreed that data analytics for decision making is extremely important and 92% asserted data analytics for decision making will be even more important in two years (bit.ly/3PBRENs). Organizations that strategically deploy tools across their finance and accounting functions have an opportunity to better structure manual processes into more stable, accurate, repeatable, and readily auditable procedures (see Gregory Kogan, Nathan Myers, Daniel J. Gaydon, and Douglas M. Boyle, "Advancing Digital Transformation," Strategic Finance, December 2021, bit.ly/3V45v0h). [...]financial decision makers are increasingly expected to engage data analytics to enhance decision making and create more efficient processes. Deployment/communication It's very important to assign responsibilities to team members (e.g., business analysts establish requirements, IT specialists gather required data, and data scientists develop and test advanced modeling techniques) with the requisite skills that vary among the phases. [...]unstructured data is data that has no uniform structure and typically isn't text-based, for example, image or sound files.
Keywords: Business And Economics--Accounting; Data analysis; Data mining; Decision making; Decision support systems; Enterprise resource planning; Management accounting; dept.acc; peer-reviewed; ⛔ No DOI found

How to Handle Pressure to Act Unethically - Haylon, Lisa S.; Bishop, Carol C.; Boyle, Douglas M.; Hermanson, Dana R. (Management Accounting Quarterly, 2022)
It is likely that accountants will face pressure to act unethically during their careers. We offer 10 practical steps to help financial professionals prepare for and respond to the pressure to act unethically.
Keywords: Accounting; Business And Economics--Accounting; Business And Economics--Management; Business ethics; Compliance; Conformity; Decision making; Fraud; Management accountants; Personality; Professionals; dept.acc; peer-reviewed; ⛔ No DOI found